Mengoptimalkan Potensi Ekonomi Dengan Produk Unggulan Kelompok Wanita Tani dan Identifikasi Indeks Desa Zakat di Desa Harkuning - Muhammad Gian Gianggi Pratama; Innayah Zahara; Neneng Hasanah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Community empowerment is done to improve the quality of the community in their welfare through activities that can improve the quality of the community as human resources and increase the potential of the region. One of the government programs for farmers is the holding of the Women Farmers Group (KWT) program with the aim to further improve and develop the capabilities of farmers and their families. The purpose of this community service activity is to improve the quality of product packaging for the Kelompok Wanita Tani (KWT) by giving product logos. In addition, there is the Zakat Village Index (IDZ) activity to find out Haurkuning village classified as a village worthy or not given zakat Keywords: community, women farmers group, zakat village index